Strategic Human Resource Interventions for Effective Change Management in Organisations - Coffie, Georgia Marfo; Antwi, James (Business, Management and Economics: Research Progress Vol. 4, 2024)
This chapter examines the potential roles of Human Resources (HR) in ensuring effective change management in organisations. It specifically focuses on four key constructs from the human resources and management literature – change leadership, communication, employee engagement and employee commitment and links them to practices in a Ghanaian research organisation, the Council for Scientific and Industrial Research (CSIR). The chapter is premised on the assumption that employees, when well engaged through HR activities, can be better informed and understand the need for change during any change management process. The case study from CSIR was tested using a quantitative research design of a survey questionnaire among 64 employees and a review of institutional documents at the CSIR - Forestry Research Institute of Ghana (CSIR-FORIG). The findings show that HR functions, such as; communication, training, and monitoring of performance that make the Human Resource Manager a change agent have some setbacks at the CSIR-FORIG. This demonstrates that change management implementation in any organisation may not yield the needed outcome partly due to HR role which may not be strongly integrated into the implementation strategy of the change process. Considering the complexity in managing change this chapter suggests a more integrated approach to change management processes. Four predictor variables have been proposed to serve as a strategic framework to guide the effective change management process: active communication; change leadership; employee engagement, and employee commitment. Therefore, policy and practice implications on any change management process need to recognise the role of HR and effectively engage HR professionals in any change management strategy.